Гладиатор из будущего. Последняя битва - Поротников Виктор Петрович (Гладиатор из будущего, 2011)
Экземпляры: ф.18 (20211029) / Инвентарный номер: 3904 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 59 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445